The Application of base isolation in a power plant structure. Issue 1 (January 2021) - Fu, Yanwei
Abstract: In this paper, large general finite element software ABAQUS is used to contrast the isolation before and after the seismic performance of a large coal-fired power plants, the application of isolation technology in the main factory building structure has carried on the preliminary discussion. Through to the main factory building structure system of isolation design and comparison analysis, get the following conclusion: after using isolation technology, obviously improve the seismic performance of the structure, under the effect of earthquake resistance, the structure of the floor shear, layer displacement and acceleration were significantly decreased, and the upper structure under earthquake is basic to keep translation, isolation effect is obvious.